MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYAH MELALUI PERMAINAN KARTU HURUF ARAB DI KELOMPOK BI TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Lili Masnarita; Zulkifli Zulkifli; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : The background of this study is the lack of ability of children to recognize letters hijaiyah. Some children are still not recognize letters hijaiyah, in distinguishing letter hijaiyah, children still like to mention the letters upside down in almost the same shape and sound and some children may not thrive in the mentions and memorize the letters hijaiyah clearly Under these conditions it is necessary to attempt to improve the ability to know hijaiyah letter child is through playing cards Arabic letters. The purpose of this study was to determine the ability to recognize letters hijaiyah increase children through playing cards Arabic alphabet, Arabic alphabet how to play cards and to know the high increase occurred. This research is a classroom action research conducted in two (2) cycles. Data collection tool that is used in this study is in the form of sheets of observation and research subjects are B1 group consisting of 7 boys and 8 girls. The results showed an increase from cycle I kesiklus II. Improvement occurred, ie from before the action to the first cycle of 34.12%, the first cycle to the second cycle of 44.44% and of the prior cycle to cycle II of 93.73%. From the results of this study concluded that through playing cards Arabic letters can improve children's ability to recognize letters hijaiyah B1 kindergarten group Pembina State 1 Bangko Rokan Hilir.keywords: hijayah letters, cards arabic